Project Based Learning dengan Strategi PTK (Praktik Tugas Kelompok) untuk Meningkatkan Aktivitas Belajar IPA dalam Kondisi Pandemi Covid-19 bagi Siswa Kelas VII di SMP Negeri 4 Gunungsari - Lilik Handayani (Universitas Pendidikan Mandalika, 2022)
This study aims to increase science learning activities in the Covid-19 pandemic condition through project based learning with a group task practice strategy. This research method uses classroom action research. The research subjects were students of SMP Negeri 4 Gunungsari class VII, totaling 33 students. This research instrument uses observation sheets, questionnaires, and documentation. The data collected was then analyzed descriptively. The results of this study indicate that in the first cycle the data obtained is 55.8% and in the I.2 cycle the average value is 65.5%, while in the second cycle the average value is 85.45. %. In the first cycle, it was said that the students were not active in participating in the learning process, while in the second cycle, the students were stated to be more active in carrying out the learning process. So it can be concluded that students are more active in carrying out science learning using a project based learning model with a group task practice strategy on the material organizational structure of life in the Covid-19 pandemic conditions at SMP Negeri 4 Gunungsari.